1983
DOI: 10.1111/j.1432-1033.1983.tb07334.x
|View full text |Cite
|
Sign up to set email alerts
|

The Stereochemical Course of Nucleotidyl Transfer Catalysed by NAD Pyrophosphorylase

Abstract: NAD pyrophosphorylase catalyses nucleotidyl transfer from adenosine (R)-~'- [E-' 70]triphosphate to nicotinamide mononucleotide with inversion of configuration at the a-P giving (S)- ['70]NAD'. The simplest interpretation of this observation is that the adenylyl group is transferred directly from ATP to the co-substrate by an 'in line' mechanism. It is also shown that snake venom phosphodiesterase hydrolyses NAD ' regio-specifically at the adenylyl terminus of the pyrophosphate bond.NAD pyrophosphorylase catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…NMN adenylyltransferase activity, which is considered critical for cell survival (Hughes et al, 1983), is very low in tumor cells, representing a potential target for cancer chemotherapy (Morton, 1958;Emanuelli et al, 1995). The kinetic study results obtained for the eukaryotic enzyme are consistent with an ordered substrate addition and product release , in agreement with the stereochemical analysis conducted by Lowe and Tansley (1983). However, improved understanding of the mechanism of action of this enzyme could undoubtedly be helpful in the design of a specific inhibitor as a candidate drug for anticancer chemotherapy.…”
Section: B N M N Adenylyltransferasesupporting
confidence: 76%
“…NMN adenylyltransferase activity, which is considered critical for cell survival (Hughes et al, 1983), is very low in tumor cells, representing a potential target for cancer chemotherapy (Morton, 1958;Emanuelli et al, 1995). The kinetic study results obtained for the eukaryotic enzyme are consistent with an ordered substrate addition and product release , in agreement with the stereochemical analysis conducted by Lowe and Tansley (1983). However, improved understanding of the mechanism of action of this enzyme could undoubtedly be helpful in the design of a specific inhibitor as a candidate drug for anticancer chemotherapy.…”
Section: B N M N Adenylyltransferasesupporting
confidence: 76%
“…Experimental data seem to indicate a similarity with respect to the cations requirement between human NMNAT-1 and its thermophilic counterpart, whereas yeast isoenzymes exhibit maximal activity with Ni 2+ and Co 2+ [102 -104]. Initial-rate kinetic studies and product inhibition patterns, obtained analyzing the reaction on both directions [94], showed that the NMNAT-1 catalytic mechanism is ordered Bi-Bi in agreement with the stereochemical data [105]. Compared with the eubacterial enzyme, which appears to prefer NaMN over NMN, human NMNAT-1 seems to use both mononucleotides with the same efficiency, thus being capable of participating in both de novo and salvage pathways of NAD + synthesis [95].…”
Section: Nmnat-1supporting
confidence: 58%
“…Because there are few interactions with the enzyme that would stabilize the NMN phosphate in its bent conformation, we assume that this conformation is less favorable or less stable than the "extend-ed" conformation. The alternative bent and extended NMN conformations in the PNAT active site provided critical insight into the catalytic mechanism of PNAT, which has been proposed to use an in-line nucleophilic attack of the NMN phosphate on the ATP ␣-phosphate (47). The propensity of NMN to adopt an extended conformation would bring the NMN phosphate close to the ATP ␣-phosphate for such an attack.…”
Section: Resultsmentioning
confidence: 99%